C. S. Lewis as philosopher: truth, goodness and beauty - Baggett, David; Habermas, Gary R.; Walls, Jerry L.; Morris, Tom (IVP Academic, 2008)
Introduction: Jack of the philosophical trade / Jerry Walls -- Truth -- Lewis's philosophy of truth, goodness and beauty / Peter Kreeft -- From atheism to deism : a conversation between Antony Flew and Gary Habermas / Gary Habermas and Antony Flew -- Defending the dangerous idea : an update on Lewis's argument from reason / Victor Reppert -- Aut deus aut malus homo : a defense of C.S. Lewis's "shocking alternative"/ David Horner -- The abolition of man : C.S. Lewis's prescience concerning things to come / Jean Bethke Elshtain -- C.S. Lewis and emotional doubt : insights from the philosophy of psychology / Gary Habermas -- Goodness -- Is divine iconoclast as bad as cosmic sadist? : Lewis versus Beversluis / David Baggett -- Pursuing moral goodness : C.S. Lewis's understanding of faith / Kevin Kinghorn -- "Belief" in the writings of C.S. Lewis / David Rozema -- To reign in hell or serve in heaven : C.S. Lewis on the problem of hell and -- Enjoyment of the good / Matthew Lee -- Lewis and the necessity of gratuitous evil / Michael Peterson -- Beauty -- Evil and the cosmic dance : C.S. Lewis and beauty's place in theodicy / Philip Tallon -- Lewis's miracles and mathematical elegance / Russell Howell -- Beastly metaphysics : the beasts of Narnia and Lewis's reclamation of the medieval -- Metaphysics of participation / Michael Muth -- Lewis and Tolkien on the power of the imagination / Gregory Bassham